Social–ecological heritage and the conservation of Mediterranean landscapes under global change. A case study in Olzinelles (Catalonia) - Otero, Iago; Boada, Martí; Tàbara, Joan David (Land Use Policy, 2013)
Both biological and cultural diversities seem to be diminishing together along with the progressive interconnection of peoples and ecosystems of the earth under the rules and dynamics of global markets. This has led some conservationists and social scientists to highlight the need for enhanced knowledge on the complex interrelationships between cultural and biological diversities if successful conservation strategies are to be achieved. In this work we show how the long-term coevolution between peasants and their environment sustained habitats and species that are now declining along with rural exodus in a mountainous area of the Mediterranean, a region where the maintenance of diverse landscapes is very much related to the presence of traditional rural activities. We provide an account of agrosilvopastoral practices once performed by the local peasant community and show their embeddedness in a particular set of institutions and worldview within an adaptive social–ecological system. We argue that such practices constitute an essential social–ecological heritage entailing valuable insights for the conservation of Mediterranean landscapes under conditions of global change.
Keywords: Biodiversity; conservation; Cultural diversity; Mediterranean; Social–ecological heritage

Loss of water availability and stream biodiversity under land abandonment and climate change in a Mediterranean catchment (Olzinelles, NE Spain) - Otero, Iago; Boada, Martí; Badia, Anna; Pla, Eduard; Vayreda, Jordi; Sabaté, Santi; Gracia, Carles a.; Penuelas, Josep (Land Use Policy, 2011)
In the north rim of the Mediterranean region, where forest cover is increasing as a result of land abandonment and temperatures are rising as a result of climate change, there is increasing interest for the effects of such changes on the runoff of water courses. This is a paramount issue for the conservation of many freshwater habitats and species. In this work we studied the effects of both an increase in forest cover after depopulation and land abandonment and an increase in temperature on the runoff of a Mediterranean catchment and on the aquatic and semi-aquatic fauna species of the stream (Olzinelles valley, NE Spain). Although in our simulation no decreasing trend in runoff is detected, the monthly runoff-rainfall ratio is now 15% lower than 30 years ago, a fact that may be attributed to a drier period rather than to the small afforestation experienced by the catchment in the last decades. Other factors such as increasing temperatures, changing rainfall patterns and increasing canopy cover are discussed. The observed decrease in the water ﬂow has caused the disappearance of white-clawed crayﬁsh (Austropotamobius pallipes), Mediterranean barbel (Barbus meridionalis), chub (Squalius cephalus), European eel (Anguilla anguilla), and southern water vole (Arvicola sapidus). Our results suggest that in a progressively warmer climate, and especially after land abandonment processes, management of Mediterranean mountain areas should be oriented towards an appropriate distribution of agrarian and forest land-covers in terms of water availability. Down to the stream scale, the pools that keep water throughout the year should be conserved and extended to enhance its potential to maintain aquatic and semi-aquatic species populations
Keywords: Aquatic fauna; Land-cover change; Mediterranean catchment; Warming; Water courses